N-decane decomposition by microsecond pulsed DBD plasma in a flow reactor. (5th February 2019) - Song, Feilong; Wu, Yun; Xu, Shida; Jin, Di; Jia, Min
Abstract: N-decane decomposition with plasma to obtain prone detonation gaseous fuel is investigated by adopting fuel liquid film feeding mode at applied voltage of 10 kV and 15 kV, discharge frequency of 300–3000 Hz with interval 100 Hz. The result shows that the discharge parameters can regulate the composition and the concentration of the cracked products. When the composition of the product is unchanged, the concentration and proportion of the components can be increased as the discharge frequency becomes higher. The hydrogen concentration increases 3.4 times and 2.3 times respectively for the applied voltage of 15 kV and 10 kV as the discharge frequency is increased from 500 to 3000 Hz. However, the voltage has no effect on the proportion of the components, and increasing the voltage only increases the concentration of the species. For selectivity, raising the discharge frequency can greatly increase the species selectivity of hydrogen and acetylene that are most prone to detonate. The selectivities of hydrogen and acetylene are the highest at 15 kV and 3 kHz, reaching 18.40% and 4.22% respectively, and at this time, the selectivity of ethylene is the lowest, which is 60.4%. Besides, it is confirmed that high selectivity can be achieved at the lower specific energy input causing by low-voltage/high-frequency discharge. Through the analysis of the bond dissociation energy, there is a competitive relationship between the production of ethylene, ethane and pentane which all consume ethyl, and two possible pathways for the production of acetylene are put forward. Highlights: Plasma decomposition of n-decane liquid film was conducted in flow reactor. Detonable gas was detected in the cracking gas. The better cracking effect could be achieved at high frequency and low voltage. The reaction path of n-decane decomposition was explained. Selectivity and energy conversion ratio were analyzed.